The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1158/2159-8290.cd-20-1385
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of EGFR-Driven Lung Cancer Growth and Therapeutic Response In Vivo

Abstract: In lung adenocarcinoma, oncogenic EGFR mutations co-occur with many tumor suppressor gene alterations; however, the extent to which these contribute to tumor growth and response to therapy in vivo remains largely unknown. By quantifying the effects of inactivating 10 putative tumor suppressor genes in a mouse model of EGFR-driven Trp53-deficient lung adenocarcinoma, we found that Apc, Rb1, or Rbm10 inactivation strongly promoted tumor growth. Unexpectedly, inactivation of Lkb1 or Setd2—the strongest drivers of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 94 publications
7
64
2
Order By: Relevance
“…One of the main reasons for multi-drug resistance is the genetic and molecular heterogeneity of cancer cells ( Gottesman et al, 2002 ). The impact of genetic alterations depends on oncogenic contexts and several studies showed that dysregulations should be analyzed in a tissue- or cancer entity specific manner ( Eser et al, 2013 ; Foggetti et al, 2021 ). Therefore, to identify much needed, effective treatment strategies for PDAC, its heterogeneity needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main reasons for multi-drug resistance is the genetic and molecular heterogeneity of cancer cells ( Gottesman et al, 2002 ). The impact of genetic alterations depends on oncogenic contexts and several studies showed that dysregulations should be analyzed in a tissue- or cancer entity specific manner ( Eser et al, 2013 ; Foggetti et al, 2021 ). Therefore, to identify much needed, effective treatment strategies for PDAC, its heterogeneity needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of these oncogenes also induce lung adenocarcinoma in mice (Fisher et al, 2001;Jackson et al, 2001;Ji et al, 2006;Politi et al, 2006). Foggetti et al used a CRISPR-Cas9 based approach to screen the effects of select mutations on development of lung adenocarcinoma initiated by Egfr/Trp53 or Kras/Trp53 mutations (Foggetti et al, 2021). Loss of Rb1, but not Cdkn2A, accelerated lung cancer progression induced by Egfr/Trp53 mutation.…”
Section: Pocket Protein Tumor Suppressor Activity In the Lungmentioning
confidence: 99%
“…More recently, NGS methods have developed from these specimens, notably for EGFR status evaluation at baseline [67]. NGS approaches are of strong interest in order to detect different genomic alterations associated in genes other than EGFR, which may explain, at least partially, some primary resistance of TKIs targeting EGFR mutations [68]. It will be certainly mandatory soon to evaluate the landscape of the different genomic alterations present in several genes and to assess other biomarkers in situ for a better prediction of therapeutic response to medications targeting EGFR mutations or to alternatively provide immunotherapy to these patients [68,69].…”
Section: Biomarkers Assessed At Diagnosis With Cytological Samples And/or Liquid Biopsies Obtained From Advanced Non-squamous Non-small-cmentioning
confidence: 99%
“…NGS approaches are of strong interest in order to detect different genomic alterations associated in genes other than EGFR, which may explain, at least partially, some primary resistance of TKIs targeting EGFR mutations [68]. It will be certainly mandatory soon to evaluate the landscape of the different genomic alterations present in several genes and to assess other biomarkers in situ for a better prediction of therapeutic response to medications targeting EGFR mutations or to alternatively provide immunotherapy to these patients [68,69]. It is noteworthy that these NGS methods will be applied not only in the late stages but also in the early stages of NS-NSCLC, which would mean patients receive adjuvant TKIs according to their EGFR status [70].…”
Section: Biomarkers Assessed At Diagnosis With Cytological Samples And/or Liquid Biopsies Obtained From Advanced Non-squamous Non-small-cmentioning
confidence: 99%